Application Security in the ISO27001 Environment. - Vasudevan, Vinod (IT Governance Pub., 2008)
Application Security in the ISO27001 Environment demonstrates how to secure software applications within a best practiceISO/IEC 27001 environment and supports implementation of the PCIDSSPayment Application Security Standard.